2014
DOI: 10.15352/bjma/1381782085
|View full text |Cite
|
Sign up to set email alerts
|

Linear maps between operator algebras preserving certain spectral functions

Abstract: Let H be an infinite dimensional complex Hilbert space and let φ be a surjective linear map on B(H) with φ(I)−I ∈ K(H), where K(H) denotes the closed ideal of all compact operators on H. If φ preserves the set of upper semi-Weyl operators and the set of all normal eigenvalues in both directions, then φ is an automorphism of the algebra B(H). Also the relation between the linear maps preserving the set of upper semi-Weyl operators and the linear maps preserving the set of left invertible operators is considered. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…This problem was solved in some special cases of semi-simple Banach algebras ( [9], [12], [16], [22]). Several authors have studied linear maps which preserve the classes of semi-Fredholm operators, Fredholm operators, and the related operators in both directions ( [1], [4], [7]). It has been shown that such maps preserve the ideal of compact operators in both directions, and the maps induced by them on the Calkin algebra are Jordan automorphisms.…”
Section: Introductionmentioning
confidence: 99%
“…This problem was solved in some special cases of semi-simple Banach algebras ( [9], [12], [16], [22]). Several authors have studied linear maps which preserve the classes of semi-Fredholm operators, Fredholm operators, and the related operators in both directions ( [1], [4], [7]). It has been shown that such maps preserve the ideal of compact operators in both directions, and the maps induced by them on the Calkin algebra are Jordan automorphisms.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that the notion of semi-Fredholm operators have close relationship with compact operators. Several authors have studied the linear maps which preserve Fredholm operators, semi-Fredholm operators, or upper semi-Weyl operators in both directions (see [2], [8]). They showed that such maps preserve the ideal of compact operators in both directions, and their induced maps on the Calkin algebra are Jordan automorphisms.…”
Section: Introductionmentioning
confidence: 99%
“…They showed that such maps preserve the ideal of compact operators in both directions, and their induced maps on the Calkin algebra are Jordan automorphisms. For example, in [2], the authors discuss the linear surjective maps preserving upper semi-Weyl operators, and show that their induced maps on the Calkin algebra are Jordan automorphisms. However, the problem of determining the structure of the maps itself hasn't been solved.…”
Section: Introductionmentioning
confidence: 99%